Determinasi PDRB, Tingkat Pengangguran Terbuka, dan Pengeluaran Pemerintah terhadap Indeks Pembangunan Manusia - Hasanah, Hayatul Hasanah; Arsan Isro (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to analyze the influence of Gross Regional Domestic Product (GDP), Open Unemployment Rate (TPT), and Government Expenditure on the Human Development Index (HDI) in Central Java Province for the 2017–2022 period. The approach used is quantitative with the panel data regression method in 35 districts/cities, with the best model determined through the Chow and Hausman test, namely the Fixed Effect Model (FEM). Secondary data was obtained from the official publication of the Central Statistics Agency (BPS) of Central Java and processed using the EViews 13 software. The results of the study showed that GDP had a positive and significant effect on HDI, while TPT had a significant negative effect. Meanwhile, government spending did not show a significant impact on HDI. A determination coefficient value (R²) of 0.5704 indicates that 57.04% of the variation in HDI can be explained by the three independent variables in the model. These findings confirm that economic growth is the dominant factor in improving people's quality of life, while unemployment is a major obstacle, and the effectiveness of public spending still needs to be improved. Theoretically, this study strengthens the integration between the theories of Endogenous Growth, Human Capital, and Welfare in explaining human development based on macroeconomic indicators. Practically, the results of the study provide recommendations for local governments to strengthen development strategies based on inclusive economic growth, productive job creation, and results-based budgeting fiscal policy reforms to accelerate the improvement of HDI and community welfare in a sustainable manner.